Offense of Contempt Against Government in Law Number 1 of 2023 Concerning Criminal Law Code From Constitutionalism Perspective - Muhammad Ihsan Firdaus (Universitas Muhammadiyah Malang, 2023)
The reform of criminal law in Indonesia has gone through a long process so it came to the enactment and promulgation of Act number 1 of 2023 concerning the Criminal Law Code which revokes the colonial heritage Criminal Law Code. However, as a newly legal product, of course, there are legal issues in it, which is related to the offence of contempt against the government which includes executive, legislative and judicial powers. Specifically for contempt against the President and Vice President, a judicial review has been submitted to the Constitutional Court and ruled unconstitutional, but it has been re-enacted in the Criminal Law Code. So, based on this premise, this research analyzes how the offence of contempt against the government is in Act number 1 of 2023 concerning the Criminal Law Code and whether the offence of contempt against the government is contrary to the principles of constitutionalism. This study uses legal research methods. So, the results of this research are first, that the offence of contempt against the government is contained in Articles 218-220 concerning attacks on honour or dignity and humiliation of the government and or state institutions which are regulated in Articles 240 and 241. Second, these offences are contrary to the principle of constitutionalism which states that power must be limited so that the recognition, respect, and protection of human rights can be properly manifested. So that the state should not regulate the offence, moreover the offence related to contempt of the President and Vice President has been adjudication unconstitutional by the Constitutional Court.